Performance evalution of conventional and wiper ceramic tools when turning hardened steel [electronic resource] - 210954 Muhamad Azuan Abdul Rashid (2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Pembuatan)) - Universiti Teknologi Malaysia, 2006